Consecuencias de la migración en los hijos de Daysi de Gonzalo Ortiz Crespo - Alberca Jaya, Ruth María (2015)
The literary analysis entitled : CONSEQUENCES OF MIGRATION IN THE CHILDREN OF DAISY OF ORTIZ GONZALO CRESPO , had the overall objective ; recognize and analyze the consequences that causes the migration work within the methodological process some entity methods including the hermeneutic which was used as a specific , allowed to understand and clarify each event present in each section were used, using their own techniques of literature search documentary, it was a great help to the analysis of the work studied .The main result was obtained that the root causes of migration are : family , same disintegration that occurs when Daysi abandons his children in Zaruma ; sexual abuse in children of migrants, this unfortunately happened with Guillermina , this product was born Juan ; alcoholism and drug addiction, actually occurring in Cléber husband of Guillermina that contempt for their behavior of their children and his wife gains ; rebellious children of migrants, this result was recognized in Roberto who became depressed , not knowing that his mother left him with his aunt.In the same way he came to the conclusion that family breakdown is the main cause of migration. Consequently it is recommended that when analyzing a work that addresses migration , meet the author's life in order to have support and context references that lived for some time and to understand the message you want to convey and then identify the consequences migration brings .